The research modelling in neighbourhood quality / Norainah Abdul Rahman, Dasimah Omar and Abdul Ghani Salleh - Abdul Rahman, Norainah; Omar, Dasimah; Salleh, Abdul Ghani (Universiti Teknologi MARA, Perak, 2011)
The paper aims to explain the previous research modelling in developing neighbourhood quality for the residents' needs in their housing and neighbouring areas. The research modelling will be based on physical, social and economic elements. The elements of physical aspects are dwelling unit, facilities and services, accessibility and sun-ounding environment. Social aspects will be measured through socio-demographic, social community and social interaction. The economic aspects, on the other, hand will focus on socio-economic of the residents. In developing the neighbourhood quality, the satisfaction model has been developed either in physical model, physical and social model or physical, social and economic model. The residents will evaluate the physical attributes using the satisfaction scale. Many researches in developed countries and developing countries use different settings for the studies such as housing scheme, medium housing scheme, public housing, low cost public housing, private public housing and informal housing.